Kepemimpinan Visioner Dalam Implementasi Program Full Day School Di Madrasah Ibtidaiyah - Pratiwi, Yovi Aji; Wiyani, Novan Ardy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aims to obtain a description of the visionary leadership of the principal in the implementation of the full day school program at MI Modern Al Azhary Ajibarang. This research is a type of field research that uses a qualitative approach. The data were collected by interviewing, observing and documenting then being analyzed through the stages of data reduction, data presentation, and data verification. The results showed that there were five strategies applied in visionary leadership at MI Modern Al Azhary Ajibarang. First, to focus leadership practices on the goals of the full day school program. Second, make short-term and long-term plans for the full day school program. Third, focus on achieving the vision for a successful full day school program. Fourth, responding to various changes made by the full day school program. Fifth, respond to the needs of teachers and student guardians in the implementation of full day school.